Trends of Design Thinking Research in STEM Education: Bibliometric Analysis - Rifqi Ghufrooni (Journal of Research in Environmental and Science Education, 2024)
Research on design thinking in education is increasing from year to year. design thinking offers creative freedom to teach, serving as a guide to enhancing the STEM experience for students. The purpose of this study is to provide an up-to-date map that explains and systematizes a collection of information from the Scopus database relating to design thinking research in STEM education. The keywords used are “design thinking” AND “STEM Education”. A total of 812 documents were identified from various types of documents and years. All data were used in bibliometric analysis. The findings show that design thinking research in STEM education has increased every year with the use of English as the most widely used language. The most published type of document is the Conference Paper. The United States of America is the most productive country with the highest number of publications and citations. The most published author is Lee. CS while Ramani K got the most citations. The most influential journal is Design Studies while the most productive source is ASEE Annual Conference and Exposition. While articles written Stempfle (2002) recorded as the most cited articles. The most used author keyword in articles is design thinking.